Students' Perceptions Towards The Use of Kahoot On Learning Motivation In English Language Learning - Amalia, Tiara; Rachman, Dzul; Surya Mahyanti, Ni Wayan; Rahmawati, Yeni (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2024)
The objective of this study is to elucidate students' perspectives regarding the utilization of the Kahoot application as a learning medium to enhance their motivation. This research employed a qualitative descriptive approach, namely a case study design. The participants of this study consist of students enrolled in the English Education Department at Universitas Muhammadiyah Kalimantan Timur (UMKT) who possess specific traits. This study employed semi-structured interviews to investigate students' impression of the impact of using Kahoot on their intrinsic motivation for learning. The findings indicate that Kahoot had numerous beneficial impacts on students' learning. The students evaluated Kahoot as a captivating online game-based learning tool that enhanced their knowledge and stimulated their drive and excitement, resulting in active learning. Additionally, this study identified the difficulties encountered by students when use Kahoot, including anxiety stemming from time constraints, inadequate internet connectivity, and instances of cheating.